Desain Fuzzy Logic Controller Untuk Pengendali Pergerakan Mobile Manipulator - Putri Repina Kesuma; Tresna Dewi; RD Kusumanto; Pola Risma; Yurni Oktarina (Indonesian Society of Applied Science (ISAS), 2020)
Technology is developing more and more to facilitate human life. Technology enables automation in all areas of life, and robots are among the most frequently used machines in automation. Robots can help with human work in all fields, including agriculture. A mobile robot manipulator is a combination of a robot arm and a mobile robot so that this type of robot can combine the capabilities of the two robots. This paper discusses the design of a robot manipulator to be used in agriculture to replace farmers in the harvesting of agricultural products, such as tomatoes. This paper presents a mechanical, electrical design and uses the Fuzzy Logic Controller as artificial intelligence. The feasibility of the proposed method is demonstrated by simulation in Mobotsim.